2011
DOI: 10.1002/jcb.23112
|View full text |Cite
|
Sign up to set email alerts
|

Fasudil hydrochloride hydrate, a Rho‐kinase inhibitor, suppresses isoproterenol‐induced heart failure in rats via JNK and ERK1/2 pathways

Abstract: The Rho-kinase (ROCK) plays an important role in the pathogenesis of heart injury. Recent cellular and molecular biology studies indicated a pivotal role of the RhoA/ROCK cascade in many aspects of cardiovascular function such as heart failure, cardiac hypertrophy, and ventricular remodeling following myocardial infarction. However, the signal transduction of RhoA/ROCK and its down-stream signaling pathways remains elusive, and the mechanism of ROCK-mediated isoproterenol (ISO)-induced heart failure is still n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 41 publications
0
35
0
1
Order By: Relevance
“…This seems to be because of a side-effect of the inhibitor in the epidermis, namely the concomitant inhibition of Rok signaling and ERK phosphorylation ( Supplementary Fig. S8B), sporadically observed in other tissues (25)(26)(27). ERK inhibition by Fasudil is not observed in the forestomach (Fig.…”
Section: A B Cmentioning
confidence: 95%
“…This seems to be because of a side-effect of the inhibitor in the epidermis, namely the concomitant inhibition of Rok signaling and ERK phosphorylation ( Supplementary Fig. S8B), sporadically observed in other tissues (25)(26)(27). ERK inhibition by Fasudil is not observed in the forestomach (Fig.…”
Section: A B Cmentioning
confidence: 95%
“…Recently, it has been demonstrated that the nuclear translocation of phosphorylated ERK1/2 depends on the Rho-kinase activity. 58 Fasudil inhibits VSMC proliferation by blocking the nuclear translocation of ERK1/2. 59 All of these reports support our present study finding that treatment with fasudil inhibited the phosphorylation of Rho-kinase and ERK1/2.…”
Section: Additive and Synergistic Effects Of The Combination Therapymentioning
confidence: 99%
“…20 However, aberrations in ERK1/2 signaling are known to occur in a wide range of pathologies, including cancer, diabetes, viral infection, and cardiovascular disease. 21,22 In preliminary studies, authors have indicated that ERK1/2 is highly abundant in both SS and normal RBCs. Yet, whether this kinase remains functional in normal or SS RBCs is unknown, and an extremely critical question in the study of SCD pathophysiology.…”
mentioning
confidence: 99%